Compressive Behavior of a Novel Hexagonal Nodes-Based 3D Chiral Auxetic Structure - Dianwei Gao; Chunwei Zhang; Jianhua Zhang (Applied Sciences, 2023)
The energy absorption capacity of materials with negative Poisson’s ratio (NPR) is attracting interest from both industry and academia due to the excellent impact resistance of the local shrinkage of materials. However, understanding the compressive behavior of 3D auxetic structures at different strain rates and developing design methods are challenging tasks due to the limited literature and insufficient data. This paper presents a study on the behavior of Poisson’s ratio of an advanced 3D chiral structure, which is formed of two orthogonally positioned 2D hexagonal nodes-based chiral structures. Firstly, both theoretical analysis and numerical simulations are conducted to identify the Poisson’s ratio of 2D chiral structures. The same theoretical value of −1 is obtained for 2D chiral structures with a bending-dominated ligaments assumption. Thereafter, the Poisson’s ratio of 3D chiral structures is determined numerically using a low-speed loaded model composed of 5 × 5 × 8 3D unit cells for eliminating the boundary effects. The results show that impact velocity can strongly affect the energy absorption and deformation behavior of the proposed 3D chiral structure. Increasing the beam radius results in reduced energy absorption capability. However, the energy absorption capability of the 3D chiral structure is not sensitive to the yield strength of nodes. Impact direction affects the energy absorption performance of the 3D chiral structure, depending on the crushing strain. The research results could be used to optimize the design of the proposed novel 3D chiral honeycombs for various applications, such as impact energy absorbers and vibration-resistant dampers.